The Characteristics of Participation of the School Community in a Shared Management Model - Brito, Renato de Oliveira; Síveres, Luiz (European Journal of Sustainable Development, 2014)
The aim of the present study of a qualitative and exploratory character is to analyze what the characteristics of the school community in a shared management model are in a school of the public school network of the Distrito Federal, Brazil, which was honored with the National Award of Reference in School Management (Prêmio Nacional de Referência em Gestão Escolar) and is situated in a financial needy location. Therefore, a bibliographical review and an on-site study was used for the purpose of clarifying the informative objectives upon which successful shared management would be characterized, emphasizing the main points to be pursued and the actions that would be most suitable for this characterization. In this study, the actions and, principally, the degree of participation of the stakeholders (students, teachers, technical-administrative personnel, support staff, parents and community) were observed. The purpose was thus to revise the concepts presented or reaffirm them so as to concretize the models adopted and standards to be followed so that shared management achieves success and becomes a reality in all schools in Brazil. Keywords: shared management. Participation. School-community relationship.